Hypercholesterolemia triggers innate immune imbalance and transforms brain infarcts after ischemic stroke - Ali Ata Tuz; Nils Hoerenbaum; Özgür Ulusoy; Adel Ahmadi; Alana Gerlach; Alexander Beer; Andreas Kraus; Anja Hasenberg; Nina Hagemann; Dirk M. Hermann; Matthias Gunzer; Matthias Gunzer; et al. (Frontiers in Immunology)
Post-stroke early activation of neutrophils contributes to intensive neuroinflammation and worsens disease outcomes. Other pre-existing patient conditions can modify the extent of their activation during disease, especially hypercholesterolemia. However, whether and how increased circulating cholesterol amounts can change neutrophil activation responses very early after stroke has not been studied. In this study, we investigated the effect of high-fat diet (HFD) induced hypercholesterolemia on neutrophil activation and stroke outcome. Mice were fed with HFD or normal diet (ND) for six weeks and then induced stroke by transient occlusion of the middle cerebral artery. The activation receptors on immune cells and plasma levels of cytokines were analyzed using flow cytometry. The amount of plasma neutrophil extracellular traps (NETs) was measured using citH3-DNA complex ELISA. We found that HFD-induced cholesterolemia increased the number of circulating and splenic neutrophils in stroke mice but reduced bone marrow neutrophils compared to sham controls. After stroke neutrophils in HFD mice expressed higher levels of activation markers Ly6G and PSGL-1 (CD162) compared to ND mice. In addition, stroke led to an increased expression of the activation markers Ly6C and CD68 on monocyte/macrophages (MΦ) in HFD mice but not in ND mice. Compared to ND, HFD increased plasma levels of the proinflammatory cytokines TNF-α, IL-6, IL-23, and MCP-1 in stroke mice. Remarkably, HFD mice showed higher amounts of circulating NETs, brain-infiltrated neutrophils, and larger infarcts after stroke compared to ND mice. The existence of hypercholesterolemia with a stroke can trigger a stronger activation of neutrophils and MΦ, causing deteriorating disease outcomes.